PENGARUH RASIO PEMBAYARAN DIVIDEN DAN PENGELUARAN MODAL TERHADAP EARNINGS RESPONSE COEFFICIENTS (ERC) DENGAN ARUS KAS BEBAS SEBAGAI VARIABEL PEMODERASI - Nugraheni Risma Wijayanti; Supatmi . (Jurnal Bisnis dan Ekonomi, 2008)
The purpose of this study is to obtain empirical evidence whether dividendpayout ratio and capital expenditure influenced to earnings response coeffcients(ERC) with free cash flow as a moderating variable. The sample is drawn by a thepurposive sampling technique from whole companies listed in BEJ, exceptfinancial companies. This study had been done for 3 years, 2003-2005, andobtained 31 companies fulfilled criteria as sample. Examination of hypothesisused multiple-regression analysis with significant level about 5%. This studyprovides empirical evidence that free cash flow hasn’t impact on influencedividend payout ratio to ERC, and free cash flow also hasn’t impact on influencecapital expenditure to ERC.Keyword: Free Cash Flow, Dividend Payout Ratio, Capital Expenditure,Earnings Response Coeeficients